lomas

Right answer?

15(x^2+3x) + 7(x^2+3x) - 5(x^2+3x)

15x^2+45x+7x^2+21x + 5(-x^2-3x)

15x^2+45x+7x^2+21x-5x^2-15x

17x^2+51x

  1. 👍 0
  2. 👎 0
  3. 👁 84
asked by math
  1. x^2 + 3x is common to all terms. So we
    factor it out:
    (x^2 + 3x) (15 + 7 - 5),
    (x^2 + 3x)17,
    17(x^2 + 3x).

    Factor your answer and it wil be identical to mine.

    Alternate method:
    Let (x^2 + 3x) = a,
    15a + 7a - 5a = 17a,
    17(x^2 + 3x).

    1. 👍 0
    2. 👎 0
    posted by Henry

Respond to this Question

First Name

Your Response

Similar Questions

  1. Algebra

    I need help trying to put the correct vocabulary words when solving this problem such as grouping, factor, prime factor, GCF, and perfect square, and please check and see if I am doing this correctly. 15x^2+31x+2 In my last

    asked by Lisa on August 10, 2014
  2. math,correction

    Directions:Multiply Problem: ((x)/(3)+(3)/(4)) ((3x)/(4)-(3)/(5)) so the answer for it i got: ((20x^2+20x-36)/(80)) I worked it and I have what you have EXCEPT 29x instead of 20x. If you can't find the error, post your work and we

    asked by Jasmine20 on January 24, 2007
  3. Algebra

    I need help trying to put the correct vocabulary words when solving this problem such as grouping, factor, prime factor, GCF, and perfect square, and please check and see if I am doing this correctly. 15x^2+31x+2 In my last

    asked by Lisa on August 10, 2014
  4. Math

    Simplify I came up with 5.5 (15x^5-21x^4+21x^2)/(3x^2 ) not sure if I did this the correct way it just doesn't seem right at all.

    asked by please help me on April 16, 2011
  5. Math(Please check my work.)

    (2x-3)(x^2+5x-3)=2x+10x^2-15x+9 *Is this correct.? this is a different problem... Here's how this one works out: ......x^2 + 5x - 3 ............2x - 3 ================== ...... -3x^2 - 15x + 9 2x^3 + 10x^2 - 6x

    asked by Margie on February 5, 2007
  6. algebra

    -15(3+x)=-6x-9 -45-15x=-6x-9 -45-15x+15x=-6x+-15x-9 -45=21x-9 -45=x-9 -45/9=5 x=5 is this right

    asked by babygirl on September 7, 2011
  7. Intermediate Algebra

    Am I going in the right track? 8x -1/x + 5x - 3/2x = 16x^2 - 2x/2x^2 + 5x^2 - 3x/2x^2 16x^2 - 2x + 5x^2 - 3x/2x^2 =21x^2 - 5/2x^2 Find the LCD 6/7z- 28, 8/x^2 -4x = 7x(x-4) Simplify 3x^2 - 2x/15x-10 = x/5 Let's start by looking at

    asked by Richard on November 3, 2006
  8. algebra

    Andrew factored the expression 54x^3-30x^2+15x as 5x(9x^2-6x+3) but when Melissa applied the distributive law and multiplied out 5x(9x^2-6x+3). she got 45x^3-30x^2+15x. thus andrew's solution does not appear to check. why is this?

    asked by Crystal on February 11, 2011
  9. math

    Andrew factored the expression 54x^3-30x^2+15x as 5x(9x^2-6x+3) but when Melissa applied the distributive law and multiplied out 5x(9x^2-6x+3). she got 45x^3-30x^2+15x. thus andrew's solution does not appear to check. why is this?

    asked by Nick on February 11, 2011
  10. math

    Factor 6x^6-15x^3+21x^2

    asked by kate on January 25, 2009

More Similar Questions